Pengembangan Algoritma Caesar Cipher dalam Game-Based Learning untuk Pendidikan Kriptografi pada Anak - Putu Arya Dharma Kesuma; I Gede Surya Rahayuda (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
The decline in children's interest in learning due to easy access to games is the main reason I designed game-based learning. To make learning more engaging, presenting materials in an interactive way is essential. Game-based learning addresses this issue by packaging educational content attractively, increasing children's interest in learning. This game will introduce the world of IT to children, particularly cyber security. One key concept is cryptography, using the Caesar cipher algorithm due to its simplicity and suitability for children. The Caesar cipher enables both encryption and decryption processes, making it perfect for teaching cryptography basics. By designing the game as an interactive mystery, it aims to enhance children's learning interest and introduce them to cyber security effectively, making learning both fun and educational.